Fertility desire in northeast China amid population shrinkage differential identification and influence mechanisms - Haoming Mu; Peng Zhang (Scientific Reports)
Abstract The population of northeast China has decreased by over 10 million from 2010 to 2020, resulting in an ageing population and economic and social development challenges. The decline in population is closely related to fertility desire. Thus, this study establishes a quantitative index system for fertility desire, tailored to the three northeastern provinces of China, using data from 4155 questionnaires. It innovatively examines the ‘three-dimensional differentiation’ characteristics of this system. The study reveals that residents’ fertility desire in the three northeastern provinces exhibits a spatial pattern characterised by ‘one axis and multiple rings’, with high fertility desire values situated east of the Harbin-Changchun-Shenyang-Dalian regional development axis. Residents’ fertility desire is influenced by various factors, including educational background, family pressure, and population migration to the south, indicating a trend towards internalisation. This paper offers a reference for developing differentiated regional population policies.